2021
DOI: 10.52232/ijolida.v2i2.40
|View full text |Cite
|
Sign up to set email alerts
|

The Discourse Of Informal Education: Developing Children Characters During Covid-19 Pandemic

Abstract: Parents are the first and foremost educators in the process of child development by positioning the house into a multipurpose building full of meaning. This study aims to explore the discourse of informal education in building children's character during the coronavirus disease-19 (covid-19) pandemic. This study is descriptive-qualitative. Data collection was carried out by studying documents and literature. The results of the study showed that the emergence of Covid-19 was initially responded to normally like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…These qualities can help develop their personalities and encourage them to embrace values such as kindness and volunteering time, effort, and money to extend a helping hand to vulnerable groups in society. This finding is consistent with studies by Brata 2021 and Rubini 2021, which demonstrated that constructive social values, such as cooperation, equality, sincerity, patience, and justice, have a significant role in enhancing individuals' personalities and making them effective members of society who can benefit both themselves and others [ 140 , 141 ].…”
Section: Discussionsupporting
confidence: 91%
“…These qualities can help develop their personalities and encourage them to embrace values such as kindness and volunteering time, effort, and money to extend a helping hand to vulnerable groups in society. This finding is consistent with studies by Brata 2021 and Rubini 2021, which demonstrated that constructive social values, such as cooperation, equality, sincerity, patience, and justice, have a significant role in enhancing individuals' personalities and making them effective members of society who can benefit both themselves and others [ 140 , 141 ].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, this will affect the psychology of students which has an impact on their motivation and interest in learning. One aspect that is very important but missing in education during this pandemic is character education (Brata, Mantra, Rai, & Wartha, 2021).…”
Section: Learning Loss During the Covid-19 Pandemicmentioning
confidence: 99%
“…Cultivating children's social communication skills is not only a need for children's development but also an urgent problem to be solved in today's early childhood. Education (Brata et al, 2021). Role play games creatively reproduce real life through children's imitation and imagination, provide opportunities for children to communicate and cooperate with their peers, and help promote the development of children's communication skills.…”
Section: Social Developmentmentioning
confidence: 99%